Anatomical Variability of Intercondylar Fossa Geometry in Patients Diagnosed with Primary Anterior Cruciate Ligament Rupture. Issue 4 (22nd October 2019) - Zbrojkiewicz, David; Scholes, Corey; Zhong, Emily; Holt, Matthew; Bell, Christopher
Abstract : The aims of this study were to (1) describe the three‐dimensional characteristics and sources of anatomical variability in the geometry of the intercondylar fossa ("notch") in an anterior cruciate ligament (ACL)‐injured sample and (2) assess the relationship between patient factors and anatomical variability of the fossa in the context of impingement risk. A retrospective analysis of preoperative magnetic resonance imaging (MRI) for 49 patients with ACL rupture was performed. Scans were examined in the axial plane using an online picture archiving and communication system (PACS) viewer and fossa width and angle assessed at multiple slices, as well as anteroposterior depth, fossa height, and calculated total volume. Principal component analysis was performed to prioritize the sources of variability. A multivariate linear regression was performed to assess relationships between different patient factors, controlling for imaging parameters and principal component loadings. Geometric properties were normally distributed for all but fossa volume, height, and distal angle. Three principal components (PCs) were identified explaining 80% of total variance, shape (PC1), size in the coronal plane (PC2), and size in the sagittal plane (PC3). Patient factors were significantly ( P < 0.05) related to PC loadings; however, a substantial amount of variance in each model remained unexplained. Intercondylar fossa characteristics vary considerably within ACL‐injury patients with shape and size in coronal and axial planes, explaining most of the variance. Although patient factors are associated with anatomical characteristics, further work is required to identify the correct combination of factors accurately predicting geometry of the fossa for planning ACL reconstruction. Clin. Anat. 33:610–618, 2020. © 2019 Wiley Periodicals, Inc.